Effect of High‐Oleic Acid Soybean on Seed Oil, Protein Concentration, and Yield. Issue 5 (1st September 2014) - La, Thang C.; Pathan, Safiullah M.; Vuong, Tri; Lee, Jeong‐Dong; Scaboo, Andrew M.; Smith, James R.; Gillen, Anne M.; Gillman, Jason; Ellersieck, Mark R.; Nguyen, Henry T.; Shannon, J. Grover
ABSTRACT: Soybeans [ Glycine max (L.) Merr.] with high‐oleic acid content are desired by oil processors because of their improved oxidative stability for broader use in food, fuel, and other products. However, non‐genetically modified organism (GMO), high‐oleic soybeans have tended to have low seed yield. The objective of this study was to test non‐GMO, high‐oleic soybean lines derived from new gene combinations for seed yield and seed composition traits. Soybean lines with ∼750 to 800 g kg –1 oleic acid concentration were generated by combining mutant allele S117N FAD2‐1A from 17D and mutant allele P137R FAD2‐1B from PI 283327. Also, lines were developed by crossing M23 with a different FAD2‐1A mutation ⋅ (Jake ⋅ PI 283327) and used for comparative purposes. Forty F4:7 high‐oleic lines with these mutant FAD2‐1A and FAD2‐1B genes were compared with forty F4:7 normal oleic acid lines (∼200–250 g kg –1 ) for seed yield, five fatty acids, total oil, and protein concentration from six crosses grown in six environments. The high‐oleic genotypes averaged >790 g kg –1 oleic acid and concentrations of palmitic and linolenic acids were significantly lower (∼30% lower) in high‐oleic acid lines than in their normal oleic acid counterparts in each environment. When averaged across all locations and populations, seed yield of the high‐oleic lines derived from 17D were within 2% of the normal oleic lines but yield between high and normal oleic lines varied among populations. The high‐oleic lines averaged significantly higher in protein than normal oleic lines in all six populations. Oil was also higher in the high‐oleic lines than normal oleic lines from the 17D populations but was lower in the high‐oleic lines derived from M23. Thus, high‐oleic soybeans derived by combining mutant allele S117N FAD2‐1A allele with mutant P137R FAD2‐1B allele can have comparable yields with the potential to generate more oil with greater functionality and a higher protein meal than soybeans with normal oleic acid content.